Impacts of microplastics and the associated plastisphere on physiological, biochemical, genetic expression and gut microbiota of the filter-feeder amphioxus. (February 2023) - Cheng, Jingguang; Meistertzheim, Anne-Leila; Leistenschneider, David; Philip, Lena; Jacquin, Justine; Escande, Marie-Line; Barbe, Valérie; ter Halle, Alexandra; Chapron, Leila; Lartaud, Franck; Bertrand, Stéphanie; Escriva, Hector; et al.
Graphical abstract: Highlights: Polystyrene microplastics previously immersed in natural seawater were investigated for their toxic effects on amphioxus under starvation conditions. Starvation was shown to be an effective way to homogenize the gut microbiota of amphioxus. Significant effects were found in the change of body size and shape of amphioxus after the microplastic exposure due to the plastisphere serving as a nutrient source, which was supported by gene expression data. We detected the potential bacterial transfer of 12 ASVs from the plastisphere to the host gut microbiota. Abstract: Oceanic plastic pollution is of major concern to marine organisms, especially filter feeders. However, limited is known about the toxic effects of the weathered microplastics instead of the pristine ones. This study evaluates the effects of weathered polystyrene microplastic on a filter-feeder amphioxus under starvation conditions via its exposure to the microplastics previously deployed in the natural seawater allowing for the development of a mature biofilm (so-called plastisphere). The study focused on the integration of physiological, histological, biochemical, molecular, and microbiota impacts on amphioxus. Overall, specific alterations in gene expression of marker genes were observed to be associated with oxidative stresses and immune systems. Negligible impacts were observed on antioxidant biochemical activities and gut microbiota of amphioxus, while we highlighted the potential transfer of 12 bacterial taxa from the plastisphere to the amphioxus gut microbiota. Moreover, the classical perturbation of body shape detected in control animals under starvation conditions (a slim and curved body) but not for amphioxus exposed to microplastic, indicates that the microorganisms colonizing plastics could serve as a nutrient source for this filter-feeder, commitment with the elevated proportions of goblet cell-like structures after the microplastic exposure. The multidisciplinary approach developed in this study underlined the trait of microplastics that acted as vectors for transporting microorganisms from the plastisphere to amphioxus.